Enzymes in biofuels production - Al-Zuhair, S.; Ramachandran, K.B.; Farid, M.; Aroua, M.K.; Vadlani, P.; Ramakrishnan, S.; Gardossi, L. (Enzyme Res, 2011)
With the inevitable depletion of the nonrenewable resources of fossil fuels and due to their favorable environmental features, biofuels promise to be the preferred fuels of tomorrow. They can displace petroleum fuels and, in many countries, reduce the dependence on imported fuel. Biofuels, derived from biomass conversion, such as biodiesel, bioethanol, biohydrogen, and biogas, are sustainable and renewable sources of energy, which are also considered CO2 neutral. In addition, burning biofuels results in reduced levels of particulates, carbon oxides and sulfur oxides, emissions compared to fissile fuels.